Analisis Mutu Pelayanan Terhadap Kepuasan Pasien Rawat Jalan - Dewi, Anggara Fitri; Harokah, Ali; Gustina, Erma; Prawira, Ricky (Jurusan Keperawatan, Poltekkes Kemenkes Palembang, 2025)
Background: The increasing competition among private hospitals demands continuous improvements in healthcare service quality to meet the growing expectations of patients. Patient satisfaction increases if the hospital is able to provide quality, fast, empathetic, safe and comfortable medical services in accordance with patient expectations. Methods: This study aims to analyze the influence of service quality dimensions on outpatient satisfaction at a private hospital in Palembang City. A quantitative approach with a descriptive-analytic and cross-sectional design was applied, involving 100 respondents selected through purposive sampling, with inclusion criteria of being ≥18 years old and having received outpatient services. The research instrument was a SERVQUAL-based questionnaire. Results: The findings revealed that most respondents were female, of productive age, and had at least a senior high school education. The overall patient satisfaction rate was relatively high (86%). All dimensions of service quality showed a significant effect on satisfaction, with empathy emerging as the most dominant factor (OR = 101.4), significantly contributing to patients’ positive experiences. These results highlight the critical role of empathetic care in enhancing patient experience and satisfaction. Conclusion: The study concludes that service quality, particularly the empathy dimension, significantly influences outpatient satisfaction in the examined private hospital.